SINTESIS FASE Nd1Ba2Cu3O7-d DENGAN Ba(OH)2.8H2O SEBAGAI PENGGANTI Ba2CO3 DENGAN METODA REAKSI PADATAN DENGAN MEDIA PENCAMPUR ALKOHOL - Astina, I Gede; Sumadiyasa, M.; Artawan, I N.; Suharta, W. G. (BULETIN FISIKA; Vol 15 No 2 (2014): BULETIN FISIKA, 2014)
The phase of Nd1Ba2Cu3O7-? has been synthesized by replacing Ba2CO3 to Ba(OH)2.8H2O. The synthesis has been done by solid reaction method in air atmosphere without annealing. The samples were mixed with alcohol partially and otherwise. The characterization using x-ray radiation (XRD), that the samples have shown the diffraction pattern appropriated to the pattern of diffraction of the Nd1Ba2Cu3O7 phase with the volume fraction greater than 93% are resulted. The refinement with the software Rietica procedure shown the Nd1Ba2Cu3O7 phase in symmetry orthorombyc form and the value of c2 is less than 1.8 only on the Ba(OH)2.8H2O sample through the calcination process are produced. The superconductivity at temperatures >77K through the Meissner effect characterization and measurements of resistivity as in the temperature function on the sample are not arose. Since the required oxygen content not enough to the formation of Nd1Ba2Cu3O7 phase in high-Tc. This is shown by the crystal structure of the Nd1Ba2Cu3O7 phase in the symmetry orthorombic-II and thetragonal are formed.